Sosialisasi Pengembangan UMKM dan Edukasi Gizi untuk Penurunan Stunting di Desa Sukosari - Ibnu Charis Rachmanda; Hariani Wahyu Ningtyas; Nesa Oktavia Toligaga; Eka Salsabila Mardiani Putri; Saskia Maulina; M. Fahreza Ramadani; Zahra Fatmawati Jabir; Hidayat Sukri; Yuliana Davi; Adnan Faris Naufal; Merina Merina; Khusniyati Masykuroh (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2025)
The Community Service Program (KKN) in Sukosari Village, Jumantono District, Karanganyar Regency, which will be implemented in August 2024, aims to overcome the problem of community service by focusing on preventing stunting and empowering MSMEs. The main problems identified include the high rate of stunting among children and limited knowledge and support for local MSME actors. The main aim of this activity is to increase public awareness regarding the importance of nutritious nutritional intake to prevent stunting, strengthen the branding of MSME products, and ensure that these products meet legality standards through the creation of a Business Identification Number (NIB) and halal certification. The method applied includes several strategic steps, namely making complementary food products in the form of spinach nuggets and fruit salad which are aimed at meeting children's nutritional needs and reducing the risk of stunting. In addition, information signs on stunting prevention were installed in strategic locations such as posyandu and village halls to increase public awareness. To support MSMEs, the KKN team also designs label and banner designs aimed at increasing the attractiveness and professionalism of products, as well as providing assistance in creating NIBs and halal certification so that MSME products can meet regulatory standards. The results of this activity show an increase in public knowledge regarding the importance of nutritious food and preventing stunting, as well as an increase in the ability of MSMEs to manage and market their products. MSME players benefit from new designs that increase the attractiveness of their products, as well as legality that expands market access. Qualitatively, this activity involved the active participation of 40 women in socialization and 15 MSME actors in the design and certification process, with full support from village officials and related agencies, which ensured the success and sustainability of the program.